Synthesis, structure, and urease inhibitory activities of Co(III), Mn(II) and Zn(II) complexes with hydrazone derived from protocatechuic acid. Issue 18 (16th September 2016) - Wang, Cun-Fang; Chen, Zhi-Jian; Zhao, Ke-Dong; Chen, Xiang-Fei; Zhang, Chun-Yang; Sheng, Gui-Hua; Zhu, Hai-Liang
Abstract: [Co III (L1 )2 ·H2 O]NO3 (1 ), [Mn II (L1 )2 ·H2 O] (2 ), and [Zn II (L1 )2 ·H2 O] (3 ) with a hydrazone derived from protocatechuic acid (HL1  = C15 H13 N3 O3 ) were designed, synthesized, and characterized by C, H, N elemental analyses, single-crystal X-ray diffraction, and IR spectra, which revealed that the three complexes are similar structures. Docking study has been done. The urease inhibitory activities of the three complexes were tested. Complexes1 and3 showed strong inhibitory activity against jack bean urease with IC50 values of 45.9 and 11.64 μM. Complex2 had no obvious inhibitory activity to urease; the IC50 was > 50 μM. Abstract :